2022
DOI: 10.3389/fonc.2022.840046
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Epsilon Overexpression Is Associated With Poor Patient Outcomes in AML and Promotes Daunorubicin Resistance Through p-Glycoprotein-Mediated Drug Efflux

Abstract: The protein kinase C (PKC) family of serine/threonine kinases are pleiotropic signaling regulators and are implicated in hematopoietic signaling and development. Only one isoform however, PKCϵ, has oncogenic properties in solid cancers where it is associated with poor outcomes. Here we show that PKCϵ protein is significantly overexpressed in acute myeloid leukemia (AML; 37% of patients). In addition, PKCϵ expression in AML was associated with a significant reduction in complete remission induction and disease-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…We observed that while sorafenib suppressed ERK1/2 activation, which is one of the downstream effectors of FLT3 signaling, the activity of several protein kinase C (PKC) isoforms, including the classical isoform PKCα, the novel isoform PKCθ and the atypical isoform PKCι, were enhanced ( Figure 3 ). PKC family members are involved in various cellular events including cell proliferation, survival, differentiation, apoptosis, and therapy resistance [ 40 , 41 , 42 , 43 ]. We observed the enrichment of at least two signaling pathways that activate PKC isoforms in pathway enrichment data (Supplementary Figure S2) .…”
Section: Resultsmentioning
confidence: 99%
“…We observed that while sorafenib suppressed ERK1/2 activation, which is one of the downstream effectors of FLT3 signaling, the activity of several protein kinase C (PKC) isoforms, including the classical isoform PKCα, the novel isoform PKCθ and the atypical isoform PKCι, were enhanced ( Figure 3 ). PKC family members are involved in various cellular events including cell proliferation, survival, differentiation, apoptosis, and therapy resistance [ 40 , 41 , 42 , 43 ]. We observed the enrichment of at least two signaling pathways that activate PKC isoforms in pathway enrichment data (Supplementary Figure S2) .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to understand the disease mechanism at genetic level as well as protein level. Protein Kinase C epsilon (PKCε) is a novel member of PKC family proteins and has been known to play significant role in numerous human diseases [ 64 , 65 ]. Its aberrant expression is particularly reported in cancers such as gall bladder cancer, prostate cancer, brain tumours, and lung cancer [ 66–70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study determined eleven pathogenic variants that effected the activity of PKCε’s kinase or regulatory domains, based on the variant location. As PKCε (gene symbol: PRKCE) expression dysregulation is commonly observed feature in numerous diseases [ 64 , 71 ], the delineation of genetic mechanism behind it will further our knowledge on the mechanism of action of this gene. Therefore, in present study, variants in the UTRs of PRKCE gene were explored to determine their regulatory influence on its expression.…”
Section: Discussionmentioning
confidence: 99%
“…PKCε was found to be markedly overexpressed in patients with AML and positively correlated with reduced complete remission, disease-free survival, and enhanced resistance to the chemotherapeutic agent daunorubicin through P-glycoprotein (P-gp)-mediated drug efflux [ 43 ]. PKCε overexpression protects AML cells from mitochondrial reactive oxygen species (ROS)-inducing agents.…”
Section: Pkc Isozymes As Prognostic Biomarkers or Therapeutic Targets...mentioning
confidence: 99%